Building a Cultural Model of Excellent Service at the Polytechnic Pelayaran Surabaya in welcoming the era of Society 5.0 - Rahayu, Trisnowati; Dahri, Muhammad; Nugraha, Bugi (PT. Riset Press International, 2024)
Polytechnic Pelayaran Surabaya (POLTEKPEL) in 2019, As part of government services that have successfully gained recognition as a Zone of Integrity Free from Corruption (WBK), this agency continues to take steps to achieve the title of Clean and Serving Bureaucratic Area (WBBM), in accordance with the concepts of bureaucratic reform and good governance. After experiencing a period of becoming a WBK predicate from 2019 to mid-2023, Surabaya Poltekpel continues to develop and create new innovations so that it can achieve the WBBM title and build a culture of excellent service in welcoming the era of Society 5.0.The type of research used in this study is Mixed methods research, This research adopts a Mixed Methods Research approach that combines quantitative and qualitative methods in the process of data collection and analysis. This approach provides assumptions that make it possible to direct how to obtain data from both types of approaches. The results showed that there was a change in the mindset of public services towards the era of Society 5.0, Public services by utilizing technology that can improve the quality and efficiency of services provided.in the Surabaya Poltekpel institution environment has been implemented E-OFFICE, Innovative Service: by developing innovation in providing better and more effective services, and the existence of data-based services and information openness so that it is necessary to create a model to build a culture of excellent service at the Surabaya Shipping Polytechnic, in welcoming the era of Society 5.0